The use of UAV derived photogrammetry data as a tool for tree measurement in industrial plantation forestry with the focus on different Local maxima and Machine learning detection methods. - Zandberg, Jacobus Hugo Visser (2023)
Thesis (MSc)--Stellenbosch University, 2023.